PROSES BERPIKIR INDUKTIF-DEDUKTIF SISWA DALAM PEMECAHAN MASALAH BANGUN DATAR MELALUI ETHNOMATHEMATICS TANAM JAJAR LEGOWO - Rusmini, Rusmini; Edy, Syahputra; Elmanani, Elmanani; Armanto, Dian; Mukhtar, Mukhtar (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
This study aims to describe the Inductive-Deductive thinking process of students through Ethnomathematics Tanam Jajar Legowo in improving students’ mathematical problem-solving abilities. Data collection techniques through in-depth interviews, pretests and posttests and triangulation data. The results of the study showed that students’ inductive thinking processes through the context of planting Jajar Legowo are that students first understand the problems in the context of planting Jajar Legowo. Students solve mathematics based on context, students solve mathematical models based on context, and fourth students create solutions to context problems. Finally, students make mathematical conclusions. Furthermore, students link general concepts to create a solution to a single-point problem using a deductive thinking model. In conclusion, there are five stages of students’ inductive thinking in finding the principle of the area of ​​flat shapes plus deductive thinking to solve problems. The research method is mixed. The subjects of the study were students of SMP N 4 Percut Sei Tuan Deli Serdang. Significant results were obtained, students’ mathematical problem-solving abilities and learning motivation also increased through Ethnomathematics Planting Jajar Legowo.